PRARANCANGAN PABRIK BIODIESEL DARI MINYAK JARAK PAGAR DAN METANOL KAPASITAS 100.000 TON/TAHUN - , CHRISTINUS DA SILVA; , Prof. Ir. Arief Budiman, M.S., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Due to unstable oil price situation in the world market, many countries have been looking for alternative energy to substitute the fossil fuel. Biodiesel is one of those alternative energy, because biodiesel is a diesel fuel made from natural renewable source such as vegetable oil, animal fats and non edible plant. This biodiesel plant is using Jathropa curcas seeds as a non edible plant which proceeds by taking jathropaâs oil as the raw material. According to Journal of Biotechnology vol. 5 (10,pp 901-906), this oil contains of 88,2 % of triglyceride (TG) and 3.4 % of free fatty acids (FFA) so that methyl ester will be synthesized through two steps of reaction. First step is esterification to convert FFA to methyl ester (biodiesel) and water, while second step is trans esterification to convert TG to methyl ester and glycerol. This methyl ester plant with 100.000 ton/year capacity will be established in sub district Vemasse- Timor Leste, with total area of 21,6 ha and 181 labours. This plant will use 53.420,9011 ton/year methanol, 397.095,3835 ton/year jatrhopa curcas seeds which proceed 100.535,3543 ton/year as the main raw material. Plant location close to the sea in Vemasse, so that the source of water for utility plant unit will be derived from sea water. Calculation of economic results are fixed capital required equal to Rp 624.844.259.788,24+ US $ 19.252.595,31 and working capital equal to Rp 55.147.755.993,87 + US $ 29.257.248,93. At 100 % production rate, obtained ROI before tax of 31,00 % (Minimal reqiuirements 11 %) ROI after tax of 15,56 % , POT before tax of year 2,43 years, POT after tax years 3,91 , with lang factor at 16,60 , BEP at 49,80 % (Requirements 40 %-60%), SDP at 22,49% and 19,90 % for DCFRR. Based on datas above, biodiesel plant from Jathropa curcas oil and methanol with 100.000 ton/years capacity is potential to be studied further.